A controlled lumbar puncture procedure improves the safety of lumbar puncture - Li, Chun; Li, Miaomiao; Wang, Yixian; Li, Shaoyi; Cong, Lin; Ma, Weining (Frontiers in Neuroscience, 2023)
In order to improve the safety of lumbar puncture (LP), we designed a new type of LP needle, that is, an integrated and controlled LP needle, which can actively and accurately control the flow rate and retention of cerebrospinal fluid (CSF) during puncture, so as to achieve a controlled LP procedure.To evaluate whether a controlled LP procedure can improve the 3 comfort of LP and reduce the risk of complications associated with LP.Patients requiring LP (n = 63) were pierced with an integrated and controlled LP needle or a conventional LP needle. The differences in vital signs, symptom score, comfort, operation time, CSF loss, CSF pressure fluctuation and back pain before and after puncture were analyzed.RESULTS: An integrated and controlled LP needle (n = 35) significantly improved patients' headache symptoms before and after puncture. In addition, a controlled LP procedure significantly reduced the amount of unnecessary CSF loss (P < 0.001), shortened the time of puncture (P < 0.001), improved patient comfort (P = 0.001) and reduced the incidence of back pain (P < 0.001). For patients with high intracranial pressure (HICP), the fluctuations in pressure of the CSF were also reduced while obtaining similar amounts of CSF (P = 0.009).A controlled LP procedure avoids unnecessary CSF loss, prevents rapid fluctuations in CSF pressure in patients with HICP, and reduces the risks associated with LP.